Using some methods to solve the problem of fuzzy transportation and suggest a new method - Abbas Hussein Batikh; Sarmad Alwan Saleh (Journal of Madenat Alelem University College, 2014)
This research aims to review some methods to solve the problems of fuzzy transportation and suggest a new method. This study Have compared the proposed method with three methods published in international journals with a complete solution to these methods using the (QSB)software, and compare these results with the proposed method by giving an examples in the case of the balanced and unbalanced models. The new method is the second best method after method ranks and also used real data for the application of the methods of the three in one of factories for the production and distribution of dairy, and distribution of products to the agents in the government if the data is fuzzy